STRATEGIES USED IN VOCABULARY LEARNING OF UNIVERSITY STUDENTS - Bunjantr, Thawatchai (Phranakhon Rajabhat Research Journal : Humanities and Social Sciences, 2021)
The purpose of this study was to find out the vocabulary learning strategies (VLS) used by the first year as well as the second year English students at the department of Thai and foreign languages, Kasetsart University Chalermphrakiat Sakonnakhon Province Campus, and to compare the differences of strategies being used among them.The data were collected from 60 English students who were studying in the first and the second year in the second semester of 2016.Three instruments using in the study were questionnaire, semi-structured interview, and think-aloud method. The data from the questionnaire were analyzed by statistical procedures of percentage frequency, mean, and standard deviation, while the analysis of information from the semi-interview and think-aloud method had been done by studying participants’ opinions. According to determination strategies, it found that 96.6% of the first year students usually searched internet to check their words for accuracy, while 96.6% of the second year students usually used English- Thai dictionary for finding the meaning of the words. For social strategies, it found that 89.9% of the first year and the second year students usually asked their friends to help them for the meaning of new words. In order to remember the meaning of word in term of memory strategies, it found that 96.6% of the first year English students usually used a highlight pen to emphasize words meaning, but 89.8% of the second year students used an underline or a cycle words to help them remember meaning of new words. In the cognitive strategies, it found that 93.3% of the first year students and 89.9% of the second year students usually took a list of words in class when they wanted to understand the meaning of new words. It also found that 96.5% of the first year students usually used mobile phone to learn new vocabulary by switching language from Thai to English or English to Thai. However, 89.9% of the second year students found the meaning of English words from what they saw.